Etiology, epidemiology, clinical implications and treatment of acute bronchiolitis-a review of the literature - Boskovska, Katerina; Petrushevska-Kolekevska, Lidija; Dilberovska, Mirjana; Popova, Gorica; Stevic, Valentina (Macedonian Association of Anatomists and Morphologists, 2013)
Bronchiolitis is an acute viral infection that is one of the leading causes for hospitalization in young children. Despite the fact that etiology and clinical sings of the disease are well-known, in this article we will give summary of the latest scientific data related to the bronchiolitis. Bronchiolitis still remains an active field for research with many open questions still remains to be answered – ista recenica. Majority of bronchiolitis episodes are caused by respiratory syncytial virus and most often occur in children aged between two and 24 months. Most children get better with supportive care at home. A small number of children require hospitalization and treatment with oxygen and hydration.
Keywords: bronchiolitis; RSV; bronchodilators; corticosteroids; ribavirin